2017
DOI: 10.1007/s40609-017-0085-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Violence, Perceived Stigma, and Other Work-Related Stressors on Depressive Symptoms Among Women Engaged in Sex Work

Abstract: While the physical health risks of sex work have been well documented, fewer studies have explored mental health risks associated with sex work. This study examined rates of depressive symptoms and associated risk factors among women engaged in sex work in Mongolia (n=222), a country experiencing significant economic and social development and where mental health infrastructure is in its infancy. A linear regression analysis indicated that significant risk factors for depressive symptoms included paying partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 50 publications
4
21
1
9
Order By: Relevance
“…Seventeen studies reported on associations between mental health problems and violence experience [ 30 , 34 , 36 , 37 , 39 , 43 , 44 , 46 , 49 , 52 , 53 , 57 , 59 , 75 , 79 , 80 , 82 ], usually by an intimate partner or a client ( Table 2 ). Measures of violence varied by timeframe (recent versus ever), typology (physical, sexual, emotional) and perpetrator (client, intimate partner, etc.).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seventeen studies reported on associations between mental health problems and violence experience [ 30 , 34 , 36 , 37 , 39 , 43 , 44 , 46 , 49 , 52 , 53 , 57 , 59 , 75 , 79 , 80 , 82 ], usually by an intimate partner or a client ( Table 2 ). Measures of violence varied by timeframe (recent versus ever), typology (physical, sexual, emotional) and perpetrator (client, intimate partner, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 56 studies, 14 scored as strong quality, 34 scored as moderate, and 8 scored as weak (S3 Text). Sixteen studies (14 moderate; 2 weak) selected participants based on harmful alcohol or drug use (n = 9) [24,26,31,33,34,[37][38][39][40], or positive [32,41] or negative [29,[42][43][44][45] HIV status (n = 5), and were excluded from the meta-analyses (regardless of CEBM score) to avoid biasing the pooled estimates. Analyses used a variety of validated scales and cut-off points to assess mental disorders (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…One recent study with women engaged in sex work in Ulaanbaatar found that 60.4% were at high risk for depression. Furthermore, variables such as harmful alcohol use, sexual violence, lack of social support, and perceived social stigma were identified as risk factors for depression among sex workers in Mongolia (Carlson et al, 2016). …”
Section: Introductionmentioning
confidence: 99%